The Dynamic Effects of Aggregate Demand, Supply and Oil Price Shocks - Hilde Christiane Bjørnland (Statistics Norway, Research Department, 1996)
This paper analyses the dynamic effects of aggregate demand, supply and real oil price shocks on real output and unemployment. Oil price shocks are included explicitly in the model, to investigate their role in explaining periods of global recessions. The different structural disturbances are identified by imposing long-run and short-run restrictions on a vector autoregressive model. The analysis is applied to Germany, Norway, United Kingdom and United States. For all countries except Norway, an adverse oil price shock has had a negative effect on output in the short run, and for US, the effect is negative also in the long run. However, whereas the first oil price shock was the most important factor behind the severity of the recession in the middle 1970s, adverse demand and supply shocks were more important than the second oil price shock in explaining the recession in the early 1980s. For Norway, a small oil exporting country, an adverse oil price shock stimulates the economy, although in the long run, the effect is most likely zero.
Keywords: C22; C32; E32; O57; 330; Oil price shocks; permanent and trasitory components; structural change; unit root; vector autoregression.